The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1152/ajprenal.90005.2013
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the Notch and PI3K/Akt pathways in high glucose-induced podocyte apoptosis

Abstract: Podocyte apoptosis contributes to the pathogenesis of diabetic nephropathy (DN). However, the mechanisms that mediate high glucose (HG)-induced podocyte apoptosis remain poorly understood. Conditionally immortalized mouse podocytes were cultured in HG medium. A chemical inhibitor or a specific short-hairpin RNA (shRNA) vector was used to inhibit the activation of the Notch pathway and the PI3K/Akt pathway in HG-treated podocytes. Western blotting and real-time PCR were used to evaluate the levels of Notch, PI3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 34 publications
2
61
0
Order By: Relevance
“…A previous study indicated that PI3K/Akt signaling pathway activation occurs in association with DN, and high sugar or transforming growth factor-β1 levels can cause changes to certain podocyte proteins such as ZO-1 and CD2AP by activating this pathway (27). Glomerular p-Akt expression in patients with DN has been observed to be increased with aggravation of the disease, although in severe lesions its expression is decreased and the expression of its negative regulation gene PTEN is gradually decreased with the increase of glomerular lesions; these results suggest that the PI3K/Akt signaling pathway is important in the development of early DN lesions (10,27). The present study found that emodin significantly promoted p-Akt protein expression in the rats with DN.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study indicated that PI3K/Akt signaling pathway activation occurs in association with DN, and high sugar or transforming growth factor-β1 levels can cause changes to certain podocyte proteins such as ZO-1 and CD2AP by activating this pathway (27). Glomerular p-Akt expression in patients with DN has been observed to be increased with aggravation of the disease, although in severe lesions its expression is decreased and the expression of its negative regulation gene PTEN is gradually decreased with the increase of glomerular lesions; these results suggest that the PI3K/Akt signaling pathway is important in the development of early DN lesions (10,27). The present study found that emodin significantly promoted p-Akt protein expression in the rats with DN.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a previous study from our group already demonstrated the participation of MAPK, ErbB, and Wnt signaling pathways during renal damage progression and their modulation after treatment with cytoprotective and anti-oxidant molecules (28). Moreover, different studies have established an interesting interplay between the Notch–PI3K/Akt and mTOR–PI3K/Akt pathways in the regulation of renal cells physiology (2931). In line with this evidence, our results here demonstrated a strict association between differentially modulated miRNAs with regulatory pathways linked to positive modulation of transcription-dependent biological process, thereby highlighting the role of MSCs and MVs to restore normal renal function after AKI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Notch signaling in hepatocytes is increased in response to high sugar concentrations [181] and hyperglycemia induced Jagged1 expression in endothelium was proposed to be an important mediator of diabetic vasculopathy [182]. Moreover, several investigators have shown that hyperglycemia elevates Notch receptor expression/signaling in cultured podocytes [183-185], and elevated Notch signaling has been linked to a loss of glomerular filtration due to a negative impact on podocyte function [186, 187]. Thus, hyperglycemic stimulation of Notch may be extremely important for understanding the pathology of diabetic nephropathy, especially since podocyte damage in diabetic kidneys has been proposed to be an early triggering event leading to other downstream renal complications [188].…”
Section: Notch and Hyperglycemiamentioning
confidence: 99%